Estudo de aspectos químicos, biológicos e biossintéticos em Piper fuligineum Kunth(Piperaceae) - Mazzeu, Bruna Fonseca [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The chemical profile of leaves and fruits of Piper fuligineum was analyzed by high performance liquid chromatography. The chemical composition of medium polarity related to leaves and fruits showed great similarity. The analysis also showed that the chemical composition of the fruits was more complex, mainly due to the presence of more polar substances. These analyzes allowed the selection of the leaves of P. fuligineum to continue the chemical studies. The chemical studies of the leaves of Piper fuligienum resulted in the isolation of six compunds, including two kavalactones (4- methoxy-6- [(E)-2-phenyl -vinyl] -2H-pyran-2-one and 6-(1,2-dihydroxy-2-phenyl- ethyl)-4-methoxy-2H- pyran-2-one), one chromanone (methyl-2,2-dimethyl-4-oxo-6- cromanacarboxylate) and two prenylated derivatives of benzoic acid (methyl-4-hydroxy-3-(3-methyl-2- buten-1-yl) benzoate and methyl-4-methoxy-3-(3-methyl -2-butenoyl) benzoate. The chemical structures of the isolated compounds were determined using spectrometric techniques, including 1D and 2D NMR. All compounds were described for the first time in Piper fuligineum, and the compound 4 is a new natural product. The ethanolic leaf extract and fractions obtained from P. fuligineum were evaluated for trypanocidal potential against epimastigote form of Trypanosoma cruzi Y strain, showing promising activity of the ethanol extract with IC50 of 26.67 g.mL-1 compared with the positive control benznidazole, with IC50 of 11.11 g.mL-1. The ethyl acetate extract, the chloroform fraction and substance 1 underwent antifungal drugs against fungi Candida albicans, C.krusei, C. tropicalis, C. parapsilosis and Cryptococcus neoformans yeast. The extract showed strong activity against the fungus Candida tropicalis and moderate activity against fungi C. krusei, C. parapsilosis and Cryptococcus neoformans yeast while the chloroform fraction showed strong activity against the fungus C. krusei, and moderate activity against...

O perfil químico de folhas e frutos de Piper fuligineum foi analisado por cromatografia líquida de alta eficiência. A composição química de média polaridade dos dois órgãos vegetais apresentou semelhança. As análises demonstraram também que os frutos apresentavam composição química complexa, principalmente devido a presença de substâncias de maior polaridade. Essas análises permitiram selecionar as folhas de P. fuligineum para dar continuidade aos estudos químicos. Estes estudos resultaram no isolamento de cinco substâncias, sendo duas kavalactonas: (E)-6-(8-feniletil)-4-metoxi-2H-piran-2-ona e 6-(2-fenil-7,8-diidroxetil)-4-metoxi-2H-piran-2-ona; uma cromanona: (2,2-dimetil-4-oxocromano-6-carboxilato de metila) e dois derivados prenilados do acido benzoico: 4-hidroxi-3-(3-metilbutil-2-en-1-il)benzoato de metila e 4-metoxi-3-(3-metil-1-oxobut-2-en-1-il) benzoato de metila. As estruturas químicas das substâncias foram determinadas utilizando técnicas espectrométricas, incluindo RMN 1D e 2D. Todas as substâncias estão sendo descritas pela primeira vez em Piper fuligineum. A substância 4 é inédita como produto natural. O extrato etanolico das folhas e as frações obtidas de P. fuligineum foram avaliadas quanto ao potencial tripanocida frente à forma epimastigota da cepa Y de Trypanosoma cruzi, mostrando promissora atividade do extrato etanólico com IC50 de 26,67 g.mL-1 quando comparado com o controle positivo, benznidazol, com IC50 de 11,11 g.mL-1. O extrato acetato de etila, a fração clorofórmica e a substância 1 foram submetidos a testes antifúngicos frente aos fungos Candida albicans, C.krusei, C. tropicalis, C. parapsilosis e a levedura Cryptococcus neoformans. O extrato apresentou forte atividade frente ao fungo Candida tropicalis e moderada atividade frente aos fungos C. krusei, C. parapsilosis e a levedura Cryptococcus neoformans, enquanto a fração clorofórmica apresentou forte atividade frente ao...
Keywords: Quimica organica; Biossintese; Produtos naturais; Ressonancia magnetica nuclear; Natural products